Water regime affects soil N2O emission and tomato yield grown under different types of fertilisers - Vitale, Luca; Tedeschi, Anna; Polimeno, Franca; Ottaiano, Lucia; Maglione, Giuseppe; Arena, Carmen; De Marco, Anna; Magliulo, Vincenzo (Italian Journal of Agronomy, 2017)
Tomato plants were subjected to three fertilisation treatments (M: mineral fertiliser; DMPP: mineral fertiliser + 3,4- dimethylpyrazole phosphate; OM: NKP + organic animal manure) in combination with two water regimes (100% and 50% evapotranspiration). Plant biomass, fruit production, nitrogen use efficiency (NUE) and N uptake, maximal PSII photochemical efficiency, Fv/Fm and cumulative soil N2O emission were determined. Well-watered OM plants showed higher values of biomass, fruit production, NUE and N uptake than M and DMPP plants; cumulative N2O fluxes were lower in DMPP plots than in M and OM plots. The reduced water supply determined a drop in crop biomass, fruit production, NUE and N uptake, and cumulative N2O fluxes in M and OM treatments that were higher in OM plots, whereas it determined a significant rise in cumulative N2O fluxes in DMPP plots that was lower in absolute term compared to M and OM plots recorded under well-water irrigation. It can be concluded that DMPP added-fertiliser has a good performance in semiarid environment resulting a better nitrogen source compared to conventional and organo-mineral fertilisers under reduced water supply, able to preserve crop yield and to determine soil N2O emissions (as expressed in CO2 eq) not dangerous for global environment.